2021
DOI: 10.3390/polym13203541
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, In-Vitro and In-Vivo Evaluation of Ketorolac Tromethamine-Loaded Hydrogels of Glutamic Acid as Controlled Release Carrier

Abstract: Glutamic acid-co-poly(acrylic acid) (GAcPAAc) hydrogels were prepared by the free radical polymerization technique using glutamic acid (GA) as a polymer, acrylic acid (AAc) as a monomer, ethylene glycol dimethylacrylate (EGDMA) as a cross-linker, and ammonium persulfate (APS) as an initiator. Increase in gel fraction was observed with the increasing concentration of glutamic acid, acrylic acid, and ethylene glycol dimethylacrylate. High percent porosity was indicated by developed hydrogels with the increase in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Other studies have also reported similar findings [ 85 ]. EGDMA acts as a crosslinking agent, so as the concentration of EGDMA increases, the crosslinking density of hydrogels will increase, which will reduce the porosity of the hydrogel and reduce the amount of water penetrating the mesh, leading to reduced swelling and vice versa [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have also reported similar findings [ 85 ]. EGDMA acts as a crosslinking agent, so as the concentration of EGDMA increases, the crosslinking density of hydrogels will increase, which will reduce the porosity of the hydrogel and reduce the amount of water penetrating the mesh, leading to reduced swelling and vice versa [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…A higher concentration of EGDMA results in a higher packing density in hydrogels, which reduces their porosity. Water penetration into the hydrogel network is reduced as EGDMA concentration increases, which results in a reduction in swelling [63].…”
Section: Swelling Behaviormentioning
confidence: 99%